2022
DOI: 10.3389/fpubh.2022.1047105
|View full text |Cite
|
Sign up to set email alerts
|

Associations between trajectories of social participation and functional ability among older adults: Results from the China Health and Retirement Longitudinal Study

Abstract: IntroductionFunctional ability (FA) and social participation (SP) are important indicators of healthy aging, both their trajectories are heterogeneous. It is little known about how the SP trajectories affects FA trajectories.MethodsFA was assessed by 20 items covering the ability of meeting basic needs and mobility. SP was assessed by frequency of participating in 10 social activities. Group-based trajectory modeling (GBTM) was used to identify the trajectories of FA and SP of the participants.ResultsTwo FA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Lee et al identified four distinct trajectories of BADL disability among older adults aged ≥ 75 years over 6 years period in Korea: low, moderate, high, and progressive [12]. The reasons for the differences in trajectory categories across studies may be multifaceted, such as the age composition of participants, differences in ADL measurement scales, and local cultural and lifestyle differences [36].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al identified four distinct trajectories of BADL disability among older adults aged ≥ 75 years over 6 years period in Korea: low, moderate, high, and progressive [12]. The reasons for the differences in trajectory categories across studies may be multifaceted, such as the age composition of participants, differences in ADL measurement scales, and local cultural and lifestyle differences [36].…”
Section: Discussionmentioning
confidence: 99%